Answer:
3x^2
Step-by-step explanation:
3x^2 can be factored out of each
-6x^2 = 3x^2(-2)
21x^3 = 3x^2(7x)
Answer:
B
Step-by-step explanation:
the photosynthesis the of 14 showed me by diameting the equation of the perpendicularcity of the dude with lactose intolerantcey
1049841
1053000x.003=3159
1053000-3159=1049841
Answer:
Step-by-step explanation:
Solution by substitution method
3x-4y=8
and 18x-5y=10
Suppose,
3x-4y=8→(1)
and 18x-5y=10→(2)
Taking equation (1), we have
3x-4y=8
⇒3x=4y+8
⇒x=(
4y+8)/
3 →(3)
Putting x=
(4y+8
)/3 in equation (2), we get
18x-5y=10
18(
(4y+8)
/3) -5y=10
⇒24y+48-5y=10
⇒19y+48=10
⇒19y=10-48
⇒19y= -38
⇒y=-
38
/19
⇒y= -2→(4)
Now, Putting y=-2 in equation (3), we get
x=4y+8
x=
(4(-2)+8)
/3
⇒x=
(-8+8)/
3
⇒x=
0/
3
⇒x=0
∴x=0 and y= -2
I'm going to guess B but I'm not sure